2013 American College of Rheumatology/European League Against Rheumatism Classification Criteria for Systemic Sclerosis Outperform the 1980 Criteria: Data From the Canadian Scleroderma Research Group. Issue 4 (April 2015) - Alhajeri, Hebah; Hudson, Marie; Fritzler, Marvin; Pope, Janet; Tatibouet, Solène; Markland, Janet; Robinson, David; Jones, Niall; Khalidi, Nader; Docherty, Peter; Kaminska, Elzbieta; Masetto, Ariel; et al.
Abstract : Objective: The goal of this study was to determine the sensitivity of the new 2013 classification criteria for systemic sclerosis (SSc; scleroderma) in an independent cohort of SSc subjects and to assess the contribution of individual items of the criteria to the overall sensitivity. Methods: SSc subjects from the Canadian Scleroderma Research Group cohort were assessed. Sensitivity was determined in several subgroups of patients. In patients without the criterion of skin thickening proximal to the metacarpophalangeal (MCP) joints, we recalculated sensitivity after removing the individual criterion. Results: A total of 724 SSc patients were included. Most were women (86%), mean age was 55.8 years, mean disease duration was 10.9 years, and 59% had limited cutaneous SSc (lcSSc). Overall, the sensitivity of the 2013 criteria was 98.3% compared to 88.3% for the 1980 criteria. This pattern was consistent among those with lcSSc (98.8% versus 85.6%), anticentromere antibodies (98.9% versus 79.8%), disease duration ≤3 years (98.7% versus 84.7%), and no skin involvement proximal to the MCP joints (97% versus 60%). In the latter subgroup, removing Raynaud's phenomenon and sclerodactyly from the criteria reduced the sensitivity to 77% and 79%, respectively. Removing both sclerodactyly and puffy fingers reduced the sensitivity to 62%. Conclusion: The 2013 SSc classification criteria classify more SSc patients than the 1980 criteria. The improvement in sensitivity is most striking in those with lcSSc, especially those without skin involvement proximal to the MCP joints. The addition of Raynaud's phenomenon and puffy fingers to the 2013 criteria accounts for important gains in sensitivity.